2009
DOI: 10.1111/j.1755-0998.2009.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of marine crustaceans from the Estuary and Gulf of St Lawrence: a regional‐scale approach

Abstract: Marine crustaceans are known as a group with a high level of morphological and ecological diversity but are difficult to identify by traditional approaches and usually require the help of highly trained taxonomists. A faster identification method, DNA barcoding, was found to be an effective tool for species identification in many metazoan groups including some crustaceans. Here we expand the DNA barcode database with a case study involving 80 malacostracan species from the Estuary and Gulf of St Lawrence. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 39 publications
4
82
0
1
Order By: Relevance
“…This is in line with the results of several recent studies which suggested that many widespread marine invertebrates taxa comprise genetically divergent cryptic species (Sponer and Roy 2002;Moura et al 2008;Chen and Hares 2011). Additionally, in the order Amphipoda, cryptic speciation has been widely reported, especially for gammarids (Costa et al 2009;Radulovici et al 2009;Baird et al 2011). In this sense, the study carried out by Pilgrim and Darling (2010) is particularly interesting because it provides molecular evidence of cryptic speciation in two introduced biofouling amphipods along the Pacific North American coast (COI genetic divergence ranged from 4.4 to 14 %).…”
Section: Taxonomic Issuessupporting
confidence: 78%
“…This is in line with the results of several recent studies which suggested that many widespread marine invertebrates taxa comprise genetically divergent cryptic species (Sponer and Roy 2002;Moura et al 2008;Chen and Hares 2011). Additionally, in the order Amphipoda, cryptic speciation has been widely reported, especially for gammarids (Costa et al 2009;Radulovici et al 2009;Baird et al 2011). In this sense, the study carried out by Pilgrim and Darling (2010) is particularly interesting because it provides molecular evidence of cryptic speciation in two introduced biofouling amphipods along the Pacific North American coast (COI genetic divergence ranged from 4.4 to 14 %).…”
Section: Taxonomic Issuessupporting
confidence: 78%
“…It is therefore recommended that an integrative taxonomic approach should be conducted whenever possible. Our results are in large agreement with the general performance of DNA barcoding data in marine metazoans (Bucklin et al 2011), crustaceans (Costa et al 2007) including marine amphipods and demonstrated the identification potential of an integrative approach combining morphology and genetics (Radulovici et al 2009;Havermans et al 2010Havermans et al , 2011). …”
Section: Species Inventory and Identificationsupporting
confidence: 78%
“…To illustrate, Shih et al (2009) used genetic barcodes to distinguish six species of fiddler crabs of the genus Uca in the Indian Ocean. In another study, Radulovici et al (2009) barcoded 87 crustacean species, most of which were shrimps, and the study showed the utility of the barcoding approach in diagnosing marine crustaceans. Genetic barcoding can also be particularly useful for identifying marine invertebrate juveniles and larvae, which are difficult to distinguish morphologically.…”
Section: Introductionmentioning
confidence: 99%